UPAYA MENINGKATKAN KEMAMPUAN BACA AL-QUR’AN MELALUI METODE TALAQQI DI KELAS X TEKNIK OTOMOTIF 4 SMK TAKHASSUS AL-QUR’AN WONOSOBO - Ahmad Robihan; Hayatuddin .; Muhammad Sabiqul Khoir (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2022)
Takhassus Al-Qur'an Vocational School Wonosobo is one of the schools that implements Al-Qur'an education for its students. Based on initial observations at the Takhassus Al-Qur'an Vocational School, Wonosobo, several students in reading the Al- Qur'an were still not proficient; some paused and made mistakes, both in terms of the makhrojul letters, the nature of the letters, and the laws of reading Tajweed. Apart from that, teacher in teaching Al-Qur'an also do not use special method. Researcher observed that students' Al-Qur'an reading skills must be improved, and teacher needs appropriate method to encourage students to improve their ability to read Al-Qur'an. The aim of this research is to determine efforts to improve reading Al-Qur'an through the Talaqqi method in classes X TO 4 of SMK Takhassus Al-Qur'an Wonosobo. The method used, is Classroom Action Research model, in which researcher and teacher plan, implement, observe, and reflect on actions in a collaborative and participatory manner, which aims to improve the quality of the classroom learning process over several cycles. The result of this research is that the application of the Talaqqi method at the Takhassus Al-Qur'an Vocational School, Wonosobo, was carried out by a teacher who read the Al-Qur'an first while the students listened, then imitated until they were accuretly, fluent, and according to the rules of the reading. This effort can improve teacher effectivenes of activities learning process and also the activeness of students in the teaching and learning process. Teacher activities in cycle I were categorized as